ANALISIS PERBANDINGAN KINERJA BANK NASIONAL, BANK CAMPURAN DAN BANK ASING DALAM RANGKA MENGHADAPI MASYARAKAT EKONOMI ASEAN (MEA)(Studi pada Sektor Perbankan yang Listing di BEI Periode Tahun 2010-2014) - MUZARLIS, AGNES FEBRIKA; Efni, Yulia; Savitri, Enni (Jurnal Tepak Manajemen Bisnis, 2016)
Bank performance appraisal is based on bank financial report itself. The financial report can be form balance report which give information about the financial position to the outside of bank that can be used of eksternal to assess the level of risk exist in a bank. Based on ownership consist of national bank, mixture bank and foreign bank. These banks has tight compete to show a good performance to the public in order to face ASEAN Economic Community.This research aimed to analyze the financial performance difference of national bank, mixture bank and foreign bank in order to face ASEAN Economic Community at the period of 2010 to 2014 with the financial ratio consist of : Banking Ratio, Primary Ratio, Return On Assets, Economic Value Added and Market Value Added. The population in this research consist of national bank, mixture bank, and foreign bank listed on Bank of Indonesia at the period of 2010 to 2014 which amount 120 banks. Based on purposive sampling techniques, the number of samples that meet the criteria are as many as 30 banks (15 national banks, 6 mixture banks, and 9 foreign banks). Analysis technique that use in this research is t-test. The result of this research base on hypothesis test show that foreign bank financial performance is better than national bank and mixture bank financial performance based of Banking Ratio, Primary Ratio and Market Value Added. Then national bank financial performance is better than mixture bank and foreign bank financial performance based of Return On Assets and Economic Value Added.